2018
DOI: 10.1007/s00247-018-4074-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality and readability of online patient information regarding sclerotherapy for venous malformations

Abstract: Online information regarding sclerotherapy for venous malformations is heterogeneous in quality and breadth of information, and does not meet readability recommendations for patient information. Radiologists should be aware of and account for this when meeting patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Numerous studies have been published assessing the readability of patient education materials, with a staggering trend towards texts written above the recommended grade level. [11][12][13][14][15][16][17][18][19][20][21][22] Our online queries yielded an average readability level that greatly surpassed the recommended 6th grade reading level set by the NIH and the AMA. Among the four different readability formulas, the lowest average readability level was equivalent to an 11th grade reading level.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Numerous studies have been published assessing the readability of patient education materials, with a staggering trend towards texts written above the recommended grade level. [11][12][13][14][15][16][17][18][19][20][21][22] Our online queries yielded an average readability level that greatly surpassed the recommended 6th grade reading level set by the NIH and the AMA. Among the four different readability formulas, the lowest average readability level was equivalent to an 11th grade reading level.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 78%
“…Although a few patterns have been published regarding the difficult readability of non-profit websites, when examining the multitude of readability analyses, no clear trend emerges. [11][12][13][14][15][16][17][18][19][20][21][22] The Urology Care Foundation, a non-profit webpage, stands out as one of the lowest scored pages and thus was easily comprehensible. In a similar study, Routh et al compared internet sources between common and uncommon pediatric urology topics and found that webpages on uncommon topics like exstrophy had inferior accuracy and completeness.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Physician websites also scored the lowest overall quality (mean 2.72) and journal articles scored the highest (4.00) (►Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…An estimated 41% of the global population is connected to the Internet, and 80% of US households have access to the Internet. 1,2 It has been well documented that a growing number of patients are researching their health concerns online before seeing a health care provider [3][4][5][6] This poses a challenge to patients tasked with deciphering complex information, and to physicians who provide medical guidance in conjunct with online health care information. [3][4][5]7 Thus, health care providers are faced with this question: What kind of medical information is being provided to patients who research health concerns online?…”
mentioning
confidence: 99%
“…Consequently, patients find medical images difficult to interpret and do not enhance understanding [2]. Although many patients access additional information about their condition on the internet, this information is also often of poor quality [28].…”
Section: Patient Educationmentioning
confidence: 99%